TECHNOLOGICAL PROFILE OF SWEET SORGHUM JUICE cv. CMSXS-646 SUBMITTED TO CHEMICAL RIPENERS APPLICATION AND SAMPLING PERIODS - ALMEIDA MOREIRA, BRUNO RAFAEL; VIANA, RONALDO SILVA; MATEUS, GUSTAVO PAVAN; CUNHA, MATHEUS LUIS OLIVEIRA (International Journal of Maize & Sorghum, 2018)
ABSTRACT - There is a little information about sweet sorghum crop behavior under chemical ripeners spraying management. Therefore, the aim of this study was to assess the technological profile of sweet sorghum (cv. CMSXS-646) juice under spraying of plant growth regulators and sampling periods. A randomized complete block experimental factorial design was used, with an additional control treatment (arrangement 2x2+1), corresponding to two chemical ripeners with three-doses for each product, glyphosate (0.2, 0.4, and 0.8 l c.p. ha-1) and methyl-sulfumeturon (10, 20, and 30 g c.p. ha-1), two sampling periods (15 and 30-days after spraying - DAS) and one control treatment (water spraying). After crop harvest, stalks were milled using a hydraulic press and the derived juice was assessed for total soluble solids (°Brix), apparent sucrose (POL), purity (PRT), reducing sugars (RS), total reducing sugars (TRS), fibers (FIB) and recoverable theoretical sugars (RTS). The dataset was subjected to the Shapiro-Wilk, Fisher, Tukey, Pearson and multiple linear regression statistical tests (p<0.05). There was an interaction between causes of variation for almost all assessed characteristics except to RTS, only affected by the sampling period. As conclusion, it is possible to grow sweet sorghum (cv. CMSXS-646) till thirty-days after spraying of chemical ripeners, treated by glyphosate 0.4 l c.p. ha-1 or sulfumeturon-methyl 10 g c.p. ha-1, because these doses caused feedstock with high °Brix, POL, total reducing sugars, purity levels. Keywords: Sorghum spp., phytorregulators, plant growth regulators, glyphosate, sulfumeturon-methyl. PERFIL TECNOLÓGICO DE CALDO DE SORGO SACARINO (cv. CMSXS-646) SUBMETIDO À APLICAÇÃO DE MATURADORES QUÍMICOS E ÉPOCAS DE AMOSTRAGEM RESUMO – Há poucas informações sobre o comportamento da cultura do sorgo sacarino sob manejo de aplicação de maturadores químicos. Portanto, o objetivo desta pesquisa foi avaliar o perfil tecnológico de caldo de sorgo sacarino cv. CMSXS-646 submetido à aplicação de maturadores químicos e períodos de amostragem. Aplicou-se o delineamento de blocos inteiramente casualizados, em esquema de fatorial (2x2+1), correspondente a dois maturadores químicos com três dosagens - glifosato (0,2; 0,4 e 0,8 l p.c. ha-1) e sulfumeturon-metil (10, 20 e 30 g p.c. ha-1); dois períodos de amostragem (15 e 30 dias após aplicação - DAA); e um tratamento controle (aplicação de água). Após a colheita, destinaram-se colmos à moagem, realizada em prensa hidráulica, para extração de caldo; avaliaram-se sólidos solúveis totais (°Brix), sacarose aparente (POL), pureza (PRT), açúcares redutores (AR), açúcares redutores totais (ART), fibras (FIB) e açúcares teóricos recuperáveis (ATR). Ao conjunto de dados, aplicaram-se testes estatísticos, Shapiro- Wilk, Fisher, Tukey, Pearson e regressão múltipla, ao nível de 5% de probabilidade. Houve interação entre as causas de variação para quase todas as características, exceto ATR, influenciado, somente, pelo período de amostragem. Concluiu-se que a aplicação dos maturadores químicos glifosato 0,4 l c.p. ha-1 e sulfumeturon-metil 10 g p.c. ha-1 apresentou um incremento na qualidade da matéria-prima com alto teor de °Brix, POL, açúcares redutores totais e níveis de pureza trinta dias após a pulverização dos maturadores. Palavras-chave: Sorghum spp., fitorreguladores, reguladores de crescimento vegetal,